2013
DOI: 10.1002/jmv.23791
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Calicivirus among day-care children: Evidence of asymptomatic viral excretion and first report of GI.7 norovirus and GI.3 sapovirus in Brazil

Abstract: Caliciviruses (Norovirus and Sapovirus) are important causes of acute gastroenteritis, with Norovirus (NoV) considered the leading cause of epidemic non-bacterial acute gastroenteritis; however, molecular and epidemiological data of the circulating Calicivirus (CV) strains among day-care children are still considered scarce. The role of asymptomatic CV excretion on viral transmission also remains poorly understood. The aim of the present study was to monitor the occurrence of NoV and Sapovirus (SaV) in a day-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 55 publications
(83 reference statements)
0
12
0
1
Order By: Relevance
“…This may also be the case for HPeV3, as it is closely related to enteroviruses, and most children develop HPeV3 infection during infancy and become seropositive during childhood [11]. Analysis of stool or throat-swab samples confirmed asymptomatic infection for viruses such as enterovirus 71, [21] echovirus 18, [22] the caliciviruses (norovirus and sapovirus), [23] and 2009H1N1 influenza virus [24]. Interestingly, asymptomatic infection with enterovirus 71 was reported in household members of patients [21].…”
Section: Discussionmentioning
confidence: 74%
“…This may also be the case for HPeV3, as it is closely related to enteroviruses, and most children develop HPeV3 infection during infancy and become seropositive during childhood [11]. Analysis of stool or throat-swab samples confirmed asymptomatic infection for viruses such as enterovirus 71, [21] echovirus 18, [22] the caliciviruses (norovirus and sapovirus), [23] and 2009H1N1 influenza virus [24]. Interestingly, asymptomatic infection with enterovirus 71 was reported in household members of patients [21].…”
Section: Discussionmentioning
confidence: 74%
“…A research conducted in the state of Pará which is also located in the Amazon region, found a frequency a little higher (4.9%) among diarrheic children 17 . A recent study conducted in a day-care in Midwest Brazil detected SaVs in 4.6% of children, and the circulating genotypes were GI.1 and GI.3 19 .…”
Section: Resultsmentioning
confidence: 98%
“…Nevertheless, in Brazil, there are limited data, considering the small number of studies available 16 , 17 , 18 , 19 . Thus, the present study aimed to investigate the SaV occurrence among hospitalized children with acute gastroenteritis from Manaus, Amazonas State, and also to improve the data on the molecular epidemiology of this virus in Brazil.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, 8% were positive for NoV of 539 stool specimens obtained from 56 children aged 6-55 months who attended a daycare center in Brazil. 19 On the other hand, a Korean study 20 indicated that 3.5% and 5.5% of children younger than age 6 years from kindergartens in that country are asymptomatically NoV positive in summer and winter, respectively. On the contrary, A Danish research group 21 showed a low asymptomatic infection rate (1.5%) of Danish children younger than age 5 years.…”
Section: Discussionmentioning
confidence: 97%